PERANAN FILSAFAT ILMU UNTUK KEMAJUAN PERKEMBANGAN ILMU PENGETAHUAN DI-ERA REVOLUSI INDUSTRI 5.0 - Randi Eka Putra, Winda Trisnawati (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This study reviews aspects of the philosophy of science that focuses on aspects of the development of science in the era of the industrial revolution 5.0. The study used a qualitative research method with a literature study approach. The collection of relevant data information is taken from various library sources such as; books, journals, news, internet in accordance with the topic of discussion. The results of this study were obtained by classifying the dimensions, elements, and sub-elements of the relationship between philosophy and science, philosophy based on its character and function, the relationship between the philosophy of science and other sciences, studying philosophy, science and the industrial revolution 5.0